Determinants of Herding Behaviour on Financial Decisions: A Theory of Planned Behaviour - Marhanum Mohd Che Mohd Salleh (Journal of Islamic Management Studies, 2022)
Purpose: This study analyses factors that influence herding behaviour among university lecturers in Malaysia. Design/Methodology: Quantitative approach is adopted through questionnaires and theory of Planned Behaviour is chose to identify the significant factors that influence individuals’ herding behaviour in making financial decision with the sample of 125 university lecturers. The data were analysed using multiple regression analysis. Findings: Overall, attitude and behavioural control is found to have significant influence towards individuals’ herding behaviour. The findings from this study indicate the unfavourable attitude towards herding behaviour among lecturers which lessen the possibility of engagement of individuals in financially related herding activities. Hence, behavioural control is found significantly influenced the individuals’ herding behaviour. The findings elucidate positive impact of behavioural control towards any individuals’ financial decision including herding. It indicates that financial institutions that have strong marketing approach and skills may influence individuals’ financial decision making.